ANALISIS KESULITAN GURU DALAM IMPLEMENTASI KURIKULUM 2013 DI SDN 216 TALUNGENG KECAMATAN BAREBBO KABUPATEN BONE - andi armelia halifah putri; Makmur Nurdin; Rosmalah Rosmalah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a type of descriptive qualitative research that aims to find out. The subjects in this study were 6 class teachers at SDN 216 Talungeng. Data collection was carried out by interviews, and observations. Data analysis techniques are data reduction, data display, Conclusion Drawing/Verification. The results of this study indicate that in planning and implementing authentic assessments at SDN 216 Talungeng, Barebbo District, Bone Regency, there are still difficulties experienced by teachers in planning and implementing authentic assessments in the affective, cognitive, and psychomotor domains, but there are also several aspects that teachers carry out without any difficulties. . The conclusion of this study is that there are still some difficulties experienced by teachers in planning and implementing authentic assessments. Therefore, special attention is needed in conducting coaching and training for teachers related to authentic assessments in order to be able to assess students optimally.